Conserving the land: the resilience of riparian wetlands and river channels by a fuzzy inference system - Mah, D.Y.S.; Rosmina, Ahmad Bustami (Springer Japan, 2012)
This technical note is an attempt to embrace a fuzzy inference system (FIS) in proper functioning condition (PFC) methodology that previously involved manual calculation in river health assessment. In order to illustrate the capability of the FIS model, the riparian system along Kuap River of Kuching, Malaysia, is used as a case study. The accessibility of river water in floodplain, vegetative cover and disturbance to riverbank structure are treated as inputs, while the river health status is the consequence. The methodology showcases two steps: (1) developing fuzzy sets based on PFC criterions and (2) integrating the inputs with fuzzy rules on their influences to riparian wetlands. The modelling efforts demonstrate that the FIS-based PFC assessment can be applied successfully and provided superior performance with regard to expressing the resilience and sustainability of riparian systems by approximate reasoning and language description.